Timing of cochlear implantation in large vestibular aqueduct syndrome–a retrospective cohort analysis - Liu, Xiao; Huang, Wanting; Wang, Yunxiu; Xu, Jingjing; Xie, Lulu; Liu, Lin; Chen, Jia (Frontiers in Neurology, 2025)
IntroductionLarge vestibular aqueduct syndrome (LVAS) typically manifests fluctuating, progressive, or sudden hearing loss. Cochlear implantation (CI) is a critical intervention for LVAS patients when hearing aids (HA) no longer confer sufficient benefit. However, determining the optimal timing for CI remains challenging due to the heterogeneous and unpredictable nature of hearing loss progression, particularly when audiological criteria for CI are met, and HA can still provide benefits. This study aimed to address these complexities by analyzing real-world data on the timing of CI and clinical decision-making processes in pediatric LVAS patients.MethodsThis retrospective cohort study reviewed the medical records of 74 pediatric patients (<18 years) with LVAS who underwent CI at a tertiary care hospital in China between 2010 and 2023. Clinical data, including newborn hearing screening (NBHS) results, methods of hearing loss identification, hearing levels at the initial audiological assessment (IAA), and patterns of hearing loss progression, were analyzed. Additionally, key milestones were evaluated, including age at hearing loss identification, IAA, and CI, and the durations between these events.ResultsThe median age at CI was 4.9 years (IQR: 3.0–6.8), with a median duration from IAA to CI of 2.9 years (IQR: 1.6–5.2). Patients identified through NBHS underwent CI earlier than those identified through poor response to sound or language learning difficulties. Moreover, patients with poor performance at IAA had an earlier age at CI and shorter duration from IAA to CI. CI timing was comparable among different hearing loss progression patterns. Finally, among patients meeting CI criteria but still benefiting from HA, while those who directly underwent CI had an earlier age at implantation, their interval from IAA to CI was similar to those who initially underwent HA fitting.ConclusionThe majority of LVAS patients experience progressive hearing loss and undergo CI during early childhood. Failure of NBHS and poor auditory performance at IAA are indicative of rapid hearing deterioration. Once audiological criteria for CI are met, prolonged observation appears unnecessary. Nevertheless, further prospective longitudinal studies are warranted to refine the timing and decision-making process.